A State‐of‐Art Review of the Metal Oxide‐Based Nanomaterials Effect on Photocatalytic Degradation of Malachite Green Dyes and a Bibliometric Analysis - Ehtisham Umar; Muhammad Ikram; Junaid Haider; Walid Nabgan; Muhammad Imran; Ghazanfar Nazir (Global Challenges, 2023)
Abstract A wide range of hard contaminants in wastewater is generated from different industries as byproducts of the organic compound. In this review, various metal oxide‐based nanomaterials are employed for the photocatalytic removal of malachite green (MG) dye from wastewater. Some cost‐effective and appropriate testing conditions are used for degrading these hard dyes to get higher removal efficiency. The effects of specific parameters are considered such as how the catalyst is made, how much dye is in the solution at first, how much nanocatalyst is needed to break down the dye, the initial pH of the dye solution, the type of light source used, the year of publications, and how long the dye has to be exposed to light to be removed. This study suggests that Scopus‐based core collected data employ bibliometric methods to provide an objective analysis of global MG dye from 2011 to 2022 (12 years). The Scopus database collects all the information (articles, authors, keywords, and publications). For bibliometric analysis, 658 publications are retrieved corresponding to MG dye photodegradation, and the number of publications increases annually. A bibliometric study reveals a state‐of‐art review of metal oxide‐based nanomaterials' effects on photocatalytic degradation of MG dyes (12 years).